Effects of the intercalation rate on the layered crystal structures and stimuli-responsive color-change properties of polydiacetylene. Issue 32 (3rd August 2017) - Takeuchi, Machi; Imai, Hiroaki; Oaki, Yuya
Abstract : The layered structures and stimuli-responsive color-change properties of polydiacetylene, an organic layered material, are changed even in the partial intercalation states of the guest ions. Abstract : Intercalation chemistry has been developed mainly in inorganic layered compounds. Organic layered materials, such as layered polydiacetylene (PDA), exhibit the intercalation nature and dynamic properties. The intercalation of guest ions or molecules has the potential to control the dynamic properties through changes in the structural stability of the organic layered materials. Here we found that the partial intercalation states of the guest ions induced the changes in the layered structures and dynamic properties of PDA. The concentration of the intercalated metal ions, such as zinc ions (Zn 2+ ), was controlled in the layered PDA. Although the layered PDA without the intercalation of the guest showed irreversible color transition from blue to red at a certain temperature, the temperature-responsive and reversible color-change properties emerged from the Zn 2+ -intercalated layered PDA even at the partial intercalation states. The results indicate that the structures and dynamic properties of organic layered materials can be controlled by the partial intercalation state.